Some problems of micro parliaments in Caribbean micro states : the Montserrat case. - Fergus, Howard A. (1991)
Discusses some of the problems faced by parliamentarians who conduct the country's affairs and the difficulty of attracting a more mentally disciplined candidate. Lists five corrective strategies as (a) attractive remuneration; (b) controls on electioneering expenditure; (c) modification of the regulation banning civil servants from entering active politics; (d) electoral reform to ensure larger electoral districts; and, (e) political education.